Polar motion resonance in the prograde diurnal band. Issue 1 (25th March 2021) - Nurul Huda, I; Bizouard, C; Allain, D; Lambert, S
Summary: Until now, the polar motion resonance (PMR) complex frequency has been determined in the seasonal and retrograde diurnal band of the polar motion. In this study, this resonance is studied in the prograde diurnal band, where polar motion is mainly composed of periodic terms caused by the diurnal oceanic tide. The resonance parameters (period and quality factor) are encompassed in the frequency transfer function between generating tidal potential and polar motion, and can be estimated accordingly. To this aim, we gather three published sets of prograde diurnal terms determined from Global Navigation Satellite System (GNSS) and Very Long Baseline Interferometry (VLBI), to which we append our own estimates based upon a processing of the VLBI delays over the period 1990–2020. Then, by fitting the PMR parameters so that the prograde diurnal terms match the corresponding components of the tide generating potential, we obtained a resonance period of about 401 d and an equivalent quality factor of −22, differing from those reigning in the seasonal band ( P PMR ≈ 431 d; Q PMR ≈ 56–255) and in the retrograde diurnal band ( P PMR ≈ 380 d; Q PMR ≈ −10). Our estimates confirm strikingly the theoretical prediction derived from the tidal ocean angular momentum derived from the FES 2014 ocean tide model.